Formação continuada na escola: construindo discussões sobre as TICs nas práticas pedagógicas com professores da Secretaria Municipal de Educação de Manaus - Tavares, Adriana Nogueira (2017)
This dissertation presents an investigative-experiential research of formative aspect, with the theme: "Continued Formation in the School: constructing discussions on the TICs in the pedagogical practices with professors of the Municipal Secretary of Education of Manaus". The problematic to be investigated wants to verify the contributions that a formation in school context, specific in educational technologies, can bring to pedagogical practices. With this, the following general objective was established: to develop a continuous formation in TICs for pedagogical practices in the school context and in collaboration with a group of teachers of a school of the Municipal Network of Manaus. The specific objectives were: a) to diagnose, through a questionnaire, the use of the technologies in the school and the training processes of the participating teachers; b) develop a continuing education experience in the school about ICT for education, based on the diagnosis made; c) To analyze the contributions that the training applied by the research, has brought to the teaching learning about the educational ICTs; D) To construct a proposal of continuous training of teachers in ICTs for the school context. From this perspective, we carried out the research in the school at the Madre Tereza Municipal School in Calcutta, located in the East Zone of the city, belonging to the District II East Zone of the Municipal Education Network of Manaus, having as collaborating group teachers who teach classes in the night shift, In the Education of Young and Adults 1º and 2º segments. The research was carried out from May to August 2016, during the night shift, and the instruments that provided support for the analysis were: a diagnostic questionnaire, an evaluative questionnaire, notes in the field diary and the accomplishment of five formative meetings at the school registered in Photographic images. The answers of the questionnaires were obtained through an individual file. With the result of the diagnostic questionnaire, the structure and organization of the formative meetings with the participating group was developed, having as epistemological basis the following concepts: collaboration, reflection and knowledge construction, conceptions that contribute to delineate an autonomous, creative teaching profile And critical. From the formative experience developed with the group of participating teachers and the results generated by the evaluative questionnaire, the product of the research was reached with the title of "Formative Itinerary on ICTs for pedagogical practices". The Itinerary is organized in five formative meetings, structured in the following way: objectives, content, videos, support material and suggestions of readings for the trainer. This Itinerary has been expanded and reorganized, and can be applied to any group of teachers that wants to deal with the use of technologies for educational practices.